Manuskrip Al-Qur’an di Masjid Agung Jamik Singaraja Bali: Kajian Filologi al-Qur’an - Ahmad Syariin; Jamaluddin Jamaluddin (Alif Lam: Journal of Islamic Studies and Humanities, 2021)
The tradition of writing manuscripts began during the development of Islam that occurred in various regions of the archipelago since 5 centuries ago. The distribution of this manuscript writing occurred evenly throughout the archipelago, from Aceh, Kalimantan, Sulawesi, Java, Maluku, to Bali and Lombok. The study of the Qur'an manuscript in one area in Bali uses a philological approach. Philology is a scientific discipline that examines handwritten manuscripts or manuscripts (manuscripts), both their physical existence and their contents that provide various information about the culture of a society that made them according to their era. The purpose of this study is to understand the characteristics of the Qur'anic manuscripts and aspects of the Qur'anic manuscripts at the Jami' Singaraja Mosque. With a qualitative research method of philological and codicological approaches that examines seven manuscripts, it is concluded that there are various variations in the shape and condition of the manuscripts, the type of paper used, the thickness of the manuscripts, calligraphy/khat, illumination and so on related to the manuscripts being studied. Of the seven manuscripts of the Qur'an, some are equipped with prayers, both prayers found at the beginning of Surah at-Taubah, or prayers for completing the Qur'an. However, in this prayer category, not all of them are in the mushaf. The prayer writings at the beginning of Surah at-Taubah are only manuscripts A, manuscripts D, and manuscripts G. While the prayer for completing the Qur'an is only found in manuscripts C and manuscripts F. In addition, there are several aspects found, namely aspects of Rasm, Aspects of Waqf, Aspects of Tajweed, and Aspects of the division of texts (Hizb). First, in terms of the use of rasm, almost all of the manuscripts use rasm imla'i, it's just that there are some words in these manuscripts which are generally written in the Ottoman rasm, for example the word az-zaka>ta, all the manuscripts use the Ottoman rasm. In terms of the use of waqf punctuation marks, it only shows some signs, as stated in manuscripts A and B, which only contain mutlaq and jaiz waqaf marks for manuscript A and the addition of waqaf tam for manuscript B. As for the end sign of a verse using a circle that varies. In terms of text distribution, it includes juz', rubu', nis}f, s^mumun, and maqra'